On uniform f −statistical convergence of sequences of functions - Listán-García, M.C. (Quaestiones mathematicae, 2023)
We introduce the notions of uniform f −statistical convergence of sequences and uniform f −statistical Cauchy sequences of functions. The natural equivalence between these two notions, in Banach spaces, is proved. In doing so, we generalize and improve results of Gökhan and Güngör.